Malacostraca Podophthalmata Britanniæ 1815–1875 by William Elford Leach and the history of its fragmented publication (Crustacea: Decapoda) - Clark, Paul F.; Harrison, Keith (Zootaxa, 2021)
The present study documents the fragmented publication history of Malacostraca Podophthalmata Britanniæ by William Elford Leach, illustrated with coloured figures of all the species by James Sowerby. This work was originally proposed to consist of 12 or 14 numbers. One number was to be published every two months between the years 1815 and 1818. Although this was increased to 19 numbers its publication by James Sowerby halted at number 17 in 1820. In that year Leach had a complete nervous breakdown and, although he eventually recovered, he was retired from his post at the British Museum in 1822. Although Leach was optimistic and set out plans to complete Malacostraca, he died from cholera in 1836 near Genoa, Italy, with the work unfinished. During the early 1870s fortuitous events occurred that would lead to the publication of numbers 18 and 19 and the completion of the work. At that time William Sowerby began negotiating with Bernard Quaritch, a London publisher, for disposal of old stock from the Sowerby publishing house including Malacostraca. George Brettingham Sowerby the younger, an established naturalist and highly skilled illustrator, proposed that the Malacostraca should be updated and he prepared Nos. 18 and 19 for publication. These last two volumes of Malacostraca were finally made available by Quaritch in November 1875. The authorship of Nos. 1–17 has never been in doubt and this is the work of Leach with illustrations by James Sowerby. Among the taxa illustrated in Nos. 18 & 19 however, are species which were not known to occur in British waters when Leach was working and as such the choice of Malacostraca illustrated in 1875 differed significantly from the original proposals. Consequently the 1875 supplement should therefore correctly be credited entirely to G.B. Sowerby II and cited as Sowerby, G.B. II in Leach, W.E. (1875). Finally, because copies of the Malacostraca are not generally available, all the magnificent plates illustrated by James Sowerby and George Sowerby II are reproduced here in full colour.